Future Primary School Teachers’ Achievement Motivation in Remote Learning Process - Stramkale, Ligita (Journal of Education Culture and Society, 2022)
Thesis. The aim of the study was to determine the level of achievement motivation of future primary school teachers during remote learning, as well as to describe each of the study dimensions characterising the achievement motivation. Methods. The study involved 162 (N=162) first-course students from Latvia, two of them were male. The study raised three research questions. RQ1: At what level do students assess each of the study dimensions that characterise the achievement motivation? RQ2: What factors hinder students from taking the initiative in the study process? RQ3: How do students monitor the quality of task performance? This paper defined five study dimensions to be assessed by students: initiative, persistence, quality of task performance, self-efficacy, seizing and exploiting opportunities. Results. The study found that four of the previously mentioned dimensions were highly assessed by the students. The dimension that characterises the persistence was assessed at a medium level. The students believe that lack of time, family conditions, and full-time work accompanying their study are the most common factors that hinder learning initiatives. To monitor the quality of task performance, most students bear in mind the assessment criteria provided by the lecturer, which are used as indicators to achieve an excellent result. Conclusion. The study concluded that the students also have a high motivation for achievement when studying remotely. In further studies, it is necessary to determine if any significant changes happen in the long run related to students’ achievement motivation when remote learning continues.